Development of polyethersulfone–poly vinylidenefluoride (PES-PVDF) thin film composite membrane FOR CO2/N2 gas separation - Mohamad Hadi, Tairin (2013)
The main purpose for this study is to produce thin film composite (TFC) by using Polyethersulfone –poly (vinylidenefluoride) (PES–PVDF) for CO2/N2 gas separation. The other purpose is to investigate the segment of Poly (vinylidenefluoride) (PVDF) as the membrane support to improve the rate of permselectivity for gas separation. First, the support membrane was development consist of poly vinylidenefluoride (PVDF), N-methyl-2-pyrolidone (NMP) and water. The dope solution which is solution for support membrane for TFC membrane was prepared by using conventional and electrical heating method. The coating solution developed in this research consists of PES, N-methyl-2-pyrolidone (NMP) and water or hexane. Then, the PES solution was coated on the PVDF casted by using glass rod. The coating layer was performed on the glass plate. Permeation test was carried out by testing pure of CO2 and N2 through the TFC membrane to see the permeability and selectivity. We measure the performance of this membrane based on terms of permeability and selectivity for the CO2/N2 gas separation. PVDF was employed as a base polymer, while N-methyl pyrrolidone (NMP) was used as a solvent. The prepared TFC membrane was characterized using Scanning Electron Microscope (SEM) and Fourier Transform Infrared Radiation (FTIR) method to determine the structure and functional group of our membrane. The combination of support porosity and concentration of coating solution could lead to achieve the optimum of selectivity and permeability respectively. The CO2 should be separated from the fuel gas to reduce the CO2 emission that can cause of environmental issues like global warming, climate change and greenhouse effect.